Ruby - Ullman, Larry E. (Larry Edward), 1972- (Visual quickstart guide., 2008)
This book is for those new to programming or that know other programming languages and would like to know Ruby. The book teaches the fundamentals of object-oriented programming and starts with creating a basic program. Everything is covered such as control structures and variables, taking input, and creating output. Moving from the basic to more advanced topics, a solid understanding of Ruby is taught in logical progression. The book ends with an overview of the Web development framework, Ruby on Rails.